Technologie informacyjne wspomagające procesy logistyczne - Chomiak-Orsa, Iwona (Information Technology Supporting Logistics Processes, 2007)
The enterprise management in the area of logistics needs well organized material and information resources. In this aspect information becomes none resource than other material resources, because the possession of well organized information flow and information system permit to undertake the series of strategic decision. The quality of information is also a significant factor. That is why the pursuit of information processes improvement is a very important element in logistics management. Contemporary information technology in the IT era, logistics activity must be based on application of information technology. Without information technology it would be less effective or inefficient.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (11); 2007; nr 1156, s. 11-19